Enhancing Hackaton Practices in Software Engineering: a Neuroscience-Informed Model for TeamWell-being and Software Quality - Ramos, Alcione; Lucena, Márcia (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2025: Anais do XXXIX Simpósio Brasileiro de Engenharia de Software, 2025)
High-pressure environments in the Information Technology (IT) sector have raised increasing concerns about mental health and team performance, particularly during intensive events such as hackathons. These collaborative, time-constrained gatherings, widely used in Software Engineering, often reproduce real-world industry stressors, negatively impacting how participants think and feel during the event. This paper presents a neuroscience-informed model designed to optimize hackathon practices by integrating human factors into their planning and execution. Structured into three interdependent dimensions: (i) Sustainable Cognitive Activation, (ii) Emotional Security and Interpersonal Relationships, and (iii) Regenerative Architecture. This model promotes well-being and enhances software quality under pressure. Grounded in cognitive neuroscience and aligned with Brazil’s updated Regulatory Standard No. 1 (NR-1/2025), the proposal will be empirically validated through a controlled experimental study with randomized participant groups. The expected results include reduced stress, improved team dynamics, and higher-quality technical outcomes. Beyond hackathons, the model offers scalable strategies to foster healthier, high-performance environments in the broader IT sector.